Systematic Literature Review: E-Module Development with PBL Approach to Enhance Students' Critical Thinking and Creativity in Science Education - Adisan Adisan; Agus Ramadan; Abdul Syukur; Aris Doyan (ESENSI: Jurnal Riset Pendidikan, 2025)
Critical thinking skills are one of the core competencies in 21st-century education, especially in science learning that emphasizes analysis, evaluation, and problem solving. This study aims to identify trends and research focuses on critical thinking in the context of science education through a bibliometric approach. Data were collected from the Dimensions database using the keywords "critical thinking" and related terms in the period 2010–2024. Bibliometric analysis was conducted using VOSviewer software to map the main keywords, the network of relationships between terms, and the temporal dynamics of publications. The results show that the keywords "critical thinking", "local wisdom", "module", "STEM", and "elementary school" emerged as dominant themes. The problem-based learning (PBL) approach, integration of local wisdom values, and the use of contextual modules are the most frequently studied strategies in an effort to improve students' critical thinking skills. Temporal analysis shows a spike in publications since 2020, indicating increasing attention to the importance of developing critical thinking in the science curriculum. These findings provide strategic directions for curriculum development, learning innovation, and educational research in the future.